All-Ceramic Reconstructions - R. Mounajjed; H. Šoukalová; B. Azar; D. Černý; M. Hammal (Czech Dental Chamber, 2018)
Background: Ceramics is a mixture of one or more metallic components with a non-metallic element, usually oxygen. The result is a chemically and biochemically stable substance that is hard, firm, brittle and thermally and electrically non-conductive. These properties are used in dentistry to produce dental ceramic restorations [14]. From all-ceramic or metalloceramic crowns and bridges, inlays, onlays, veneers and implants and their abutments, and teeth intended to use with the removable dentures [15].Dental ceramics consist of a combination of amorphous glass (binder) and ceramic crystals (filler), whose relative ratio determines the final properties of the ceramic restorations [15]. Material properties: The glass is a homogeneous amorphous (not a crystalline lattice) solid mass resulting from rapid cooling of the melt, most often glassy melting sand. Its main ingredient is silicon oxide (silica) SiO2, enriched with additives such as sodium carbonate (soda) and potassium carbonate to reduce melting temperature and calcium oxide (burnt lime) for better chemical resistance. By increasing the volume of amorphous glass, the ceramic structure gains transparency, but loses its mechanical resistance. The non-crystalline glass is etchable with hydrofluoric acid, allowing the subsequent adhesion of ceramic surface to hard tooth tissue [11, 15]. Conclusions: Crystals (forming a crystalline grid) improve the mechanical properties of amorphous glass. They have the function of retarders to prevent cracks propagation and breakage of parts of ceramics. By increasing the binder and filler ratio in favor of crystals, ceramics loses transparency and becomes more resistant [11].The all-ceramic restorations are very popular in everyday dental practice. It is a very reliable material that has a high aesthetic potential and a favorable mechanical resistance. Its good prognosis, while adhering to the right technological process, opens up other options for its use.